Karakterisasi Sebaran Binomial Negatif-Binomial Negatif - Deby Handayani (LPPM Universitas Dharma Andalas, 2022)
This study discusses the convolution or the sum of independent and identical random variables, where the random variables are two distribution of Negative Binomial distribution so that the resulting distribution is known as the Negative Binomial - Negative Binomial. The purpose of this study is to find the characteristics of the distribution including the expected value, the variance value, the moment generating function and the characteristic function. This property is obtained by using theorems and lemmas that relate to the properties of a distribution. It is found that the expected value, variance value, moment generating function and characteristic function of the Negative Binomial-Exponential distribution are